Evaluation of Information Technology Investment in Telecommunications Billing Systems in South Africa - Kunver, Sudhir Dinesh (My University, 2012)
Managers in firms across the country are faced with the challenge of making key decisions regarding the justification and/or approval of IT investment on hardware and software assets, along with the associated professional services and operational support services. The appraisal of IT investments are of increasing importance to managers as economic and competitive pressures force companies to focus on cost reduction. The purpose of this research is to assess current industry practices regarding the evaluation of Information Technology (IT) investments in South Africa, specifically investments in Telecommunications Billing Systems. The organisation and industry along with the characteristics of the particular information technology being considered affects the nature of the investment evaluation criteria adopted, the evaluation techniques used and the method used for post-implementation evaluation. The sample for the research consisted of stakeholders of the Evaluation of Investments in Telecommunications Billing Systems at key network operators in South Africa, specifically stakeholders who are responsible for influencing decision-making regarding Billing Systems and those who are responsible for architecting Billing Solutions for operators at vendors. This study has shown that, while industry acknowledges the importance of Billing Systems to operators, and believes in the need for investment evaluation of billing systems, the extent of adoption of available investment evaluation techniques has been restricted, due to awareness and perceived complexity of these techniques. Based on the interviews, the study has seen that although industry has adapted its existing evaluation techniques and criteria, it seeks improved methods for evaluating intangible benefits of IT investments. The study also found that the evaluation during and after implementation is not a common practice in the industry, with resource constraints and a lack of emphasis on the importance of these evaluations being the major reasons.
MBA thesis - WBS
Keywords: Information technology; Telecommunications; Billing systems